COMPARATIVE EFFECT OF ESPRESSO COFFEE AND CAPPUCINO COFFEE ON INSOMNIA IN ADULTS: SYSTEMATIC REVIEW - Lena Maryam; Popi Sopiah; Ria Inriyana (Buletin Veteriner Udayana, 2024)
Insomnia is a disorder that occurs when a person is dissatisfied with the quantity or quality of their sleep. Insomnia can be caused by many things, including disease, environmental conditions, physical activity, mental stress, drugs, and chemicals, caffeine or coffee. Coffee is one of the most frequently consumed drinks throughout the world. Apart from having beneficial activities, caffeine also has detrimental activities, including insomnia and headaches. This study aims: To identify further research through systematic review research that compares the effect of espresso and cappuccino coffee on insomnia in adults. Method: The method used is a systematic review by identifying and evaluating literature with a quantitative research design in accordance with predetermined criteria and feasibility. The databases used include Google Scholar, Pubmed, and Systematic Scholar. Relevant articles underwent quality assessment using the JBI Critical assessment. The keywords entered are "insomnia", "espreeso coffee", "cappuccino coffee", and adults. Research shows that there are 7 articles that are relevant to the established criteria. 7 articles show that espresso coffee and cappuccino coffee have an influence or are significant on insomnia in adults. Conclusion: This study found differences in caffeine levels in espresso coffee and cappuccino. Researchers also found a significant difference between coffee and insomnia in adults. What affects insomnia the most is espresso coffee compared to cappuccino because it is mixed with milk. Suggestion: For insomnia sufferers, be aware that you can reduce coffee consumption. For families who suffer from insomnia, it is hoped that they will continue to pay attention to conditions to control or reduce drinking caffeine which will trigger insomnia. It is necessary to provide education about consuming coffee and the negative and positive effects on body health, then when is the right time to consume coffee.